Persepsi dan Pengalaman Mahasiswa Menggunakan Gamifikasi untuk Meningkatkan Motivasi dan Keterampilan Bahasa Inggris di Era Digital - Safitri, Ni Putu Dianita; Tari, Nirmala (Jurnal Simki Pedagogia, 2024)
This study aims to explore students' perceptions and experiences in using gamification to improve their motivation and English skills in the digital era. The research method used is a qualitative approach with data collection through questionnaires in the form of open-ended and closed-ended questions. Diploma II Accommodation students at the Indonesian Hospitality Management Community Academy were the subjects of this study. The results of the study indicate that the use of gamification in learning English in the digital era has a positive impact on students' motivation and English skills. Based on data obtained from closed-ended questions, the majority of students showed a high level of agreement with the use of gamification in learning English. They feel more motivated, more confident, and more interested in speaking English. In addition, the results of the study indicate that gamification features help to better understand the material, the learning process is more enjoyable, increasing enthusiasm and interest in English learning materials, and also providing comprehensive insights into the effectiveness of learning English in the digital era. The results of this study can provide valuable contributions to the development of innovative and effective learning methods in improving students' motivation and English skills in the digital era.